Penerapan Metode RAD Pada Perancangan Sistem Informasi Permohonan Data Aduan Smartmaps Berbasis Web - Lala Nilawati; Martin Martin (STMIK Budi Darma, 2023)
Current progress in the development of information technology, makes every government agency or private organization, must be able to balance and develop capabilities in terms of data and information management. Komnas HAM is one of the government agencies, which is directly related to the provision of public information to the public, requiring an information system for the process of providing this information flow. The public is allowed to submit requests for data, such as data on complaints of cases that have occurred, for which information is needed. Currently the process of requesting data is still being carried out by the public coming directly to fill out the data request form, then it will be processed by the relevant section at Komnas HAM, after the data request is approved, the requested complaint data document will be sent via POS. This system still has weaknesses, because the applicant's side cannot monitor the progress of the data application process whether it is approved or not, the applicant is only asked to wait and if the document is sent by post, the application is approved. This Web-Based Smartmaps Complaint Data Application Information System can be a solution, to facilitate the process of requesting data requested by the public. This system was designed by applying the Rapid Application Development (RAD) method in the system design stage, and the system will be built using the programming language PHP 7.3, MySQL 5.7, Nginx and PHP-FPM 7.4, Laravel 7 Framework and Bootstrap Template Design 4.0. This system, after testing using blackbox testing in its application, is proven to have provided convenience and the best service to people who have an interest in complaint data.